If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-3)=2x+3
We simplify the equation to the form, which is simple to understand
(x-3)=2x+3
Remove unnecessary parentheses
x-3=2x+3
We move all terms containing x to the left and all other terms to the right.
+1x-2x=+3+3
We simplify left and right side of the equation.
-1x=+6
We divide both sides of the equation by -1 to get x.
x=-6
| x^2-2x-1=144 | | 4t+1+3t-6t=6+3 | | (-3)=2x+3 | | 9x+14=5x-6 | | (x-1)=2x+3 | | y=9.6+0.3x | | 3p+6=2p+9 | | 8y-102+2y+6=3x | | -6.439x+.207x^2=-1.36 | | m+2.8=5.2 | | 3(2r+-1)+5=5(r+1) | | -4-28=3-4x | | (7b+1)(b-5)=0 | | -22-3r=3r-2(4r+8) | | 3(2r-1)+5=5(7+1) | | -5a^2+13ab=0 | | f-4=-3 | | 8r-7r=(-1)+12 | | 8=s+3 | | q-3=-8 | | 9(x+5)+3=48 | | 7(3+t)-5(t+2)= | | .5=.4x-.25x | | C=39.24+0.25x | | 12+n=(-1)-7 | | 3j^2-51j^2+210j=0 | | -m-9=9 | | .12x+.20(5-x)=.8 | | 5x^2+2xy+6y^2=30 | | Ln(4-3x)=7 | | 30b=90 | | 2x-4/3=6 |